Isolation and characterization of four novel Vibrio parahaemolyticus bacteriophages from oysters - Joud Aldaroub; Chrissy M. Walsky; Rylee E. Ewell; Frank O. Aylward; Ann M. Stevens; Alison Kernell Burke (PLoS ONE, 2025)
Vibrio parahaemolyticus (VP) is a bacterial pathogen found in brackish and marine water that infects many marine organisms, such as oysters and shrimp. Consumption of raw or undercooked seafood contaminated with V. parahaemolyticus is a primary cause of seafood-borne gastroenteritis in humans. Due to increasing ocean temperatures, V. parahaemolyticus contamination of oyster beds in the United States has spread up the east and west coasts to the northern-most states. Promising new research is exploring the isolation of bacteriophages against V. parahaemolyticus with a long-term goal to possibly decontaminate oyster beds, thereby expanding the harvest season and allowing for safer consumption of seafood. In this study, store-bought oysters harvested from the Chesapeake Bay in Virginia were used to isolate four bacteriophages with activity against a specific V. parahaemolyticus strain. A standard double agar overlay plaque assay was used to identify phage activity. After phage isolation, the genomes were sequenced, and transmission electron microscopy (TEM) was performed to visualize the virions. The genomes and TEM images revealed four distinct phages. Three of the phages are distinct isolates that exhibit podovirus-like morphology with short tails and genome sizes of approximately 43 kbp. One phage has siphovirus-like morphology and is a mid-sized tailed phage with a genome size of 80 kbp. Although spot tests performed with the oyster homogenates on up to 10 different V. parahaemolyticus strains recovered activity across a wide range of hosts, plaque assays with the isolated phages showed limited host range. Future work will be necessary to determine the viability of using the bacteriophages for elimination of V. parahaemolyticus in harvested oysters, treatment of aquaculture seed and spat, and/or the environment.